Perlindungan Data Privasi dalam Sistem Database Digital: Regulasi, Tinjauan Etika, dan Strategi Teknis - Nurkhaliza Nurkhaliza; Muhammad Irwan Padli Nasution (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Digital transformation in Indonesia has increased dependence on digital database systems, so that personal data protection has become a crucial issue. This research aims to analyze the urgency of protecting personal data in digital database systems in Indonesia from regulatory, ethical and technical strategy aspects. The method used is literature study and document analysis of regulations, ethical practices and data protection technology. The research results show that even though Law Number 27 of 2022 concerning Personal Data Protection (UU PDP) has been passed, its implementation still faces challenges in the form of low digital literacy, weak law enforcement, and not yet optimal monitoring infrastructure. Additionally, implementing ethical principles and technical strategies, such as encryption, access control, and privacy by design, is critical to strengthening data security. This research concludes that effective personal data protection can only be realized through synergy between strong regulations, the application of digital ethics, and adequate technical strategies, in order to safeguard individual privacy rights in the digital era.